2008
DOI: 10.1093/brain/awn250
|View full text |Cite
|
Sign up to set email alerts
|

Wayfinding in the blind: larger hippocampal volume and supranormal spatial navigation

Abstract: In the absence of visual input, the question arises as to how complex spatial abilities develop and how the brain adapts to the absence of this modality. We explored navigational skills in both early and late blind individuals and structural differences in the hippocampus, a brain region well known to be involved in spatial processing. Thirty-eight participants were divided into three groups: early blind individuals (n = 12; loss of vision before 5 years of age; mean age 33.8 years), late blind individuals (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
132
4
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(151 citation statements)
references
References 38 publications
8
132
4
7
Order By: Relevance
“…This is consistent with the hypothesis that this region stores spatial representations of the environment and enlarges as more information is stored. Interestingly, in a recent study of hippocampal volume and navigational skills in individuals with blindness, the subjects also had enlarged hippocampi and superior ability to learn new routes, and to perform pointing tasks in a maze and a spatial layout task [Fortin et al, 2008]. Additional studies have shown that limb amputation is associated with decreased gray matter in the thalamus while mathematicians have been reported to have increased gray matter in the parietal cortex [Draganski et al, 2006b;Aydin et al, 2007].…”
Section: Structural Changes In the Brain Associated With Neural Plastmentioning
confidence: 99%
“…This is consistent with the hypothesis that this region stores spatial representations of the environment and enlarges as more information is stored. Interestingly, in a recent study of hippocampal volume and navigational skills in individuals with blindness, the subjects also had enlarged hippocampi and superior ability to learn new routes, and to perform pointing tasks in a maze and a spatial layout task [Fortin et al, 2008]. Additional studies have shown that limb amputation is associated with decreased gray matter in the thalamus while mathematicians have been reported to have increased gray matter in the parietal cortex [Draganski et al, 2006b;Aydin et al, 2007].…”
Section: Structural Changes In the Brain Associated With Neural Plastmentioning
confidence: 99%
“…At the same time, hippocampal functionality has additional facets of potential relevance to PTSD. These include spatial/contextual processing (Bilkey, 2007 ;Fortin …”
Section: Introductionmentioning
confidence: 99%
“…Visual cues signaling the location of landmarks play a key role in facilitating the formation of spatial cognitive maps used for path finding in a visual setting (1,2). Despite the importance of vision in spatial cognition, the abilities to recognize a traveled route and to represent spatial information are maintained in blind individuals (3)(4)(5), probably through tactile, auditory, and olfactory cues, as well as motion-related cues arising from the vestibular and proprioceptive systems.…”
mentioning
confidence: 99%